Determinants of successful digital adoption : A Meta-Synthesis Analysis using The TOE Framework - Ni Wayan Rena Mariani; Ida Bagus Raka Suardana; Ida Ayu Oka Martini (Sharia Economic and Management Business Journal (SEMBJ), 2026)
undertake. This is a form of organizational management's response to increasingly sophisticated technological developments. However, organizations cannot simply digitize and stop there to combat disruption caused by technological developments. In line with the development of AI and increasing public enthusiasm for utilizing technology, organizations must undertake Digital Transformation. Many organizations simply stop at the digitalization process without being able to increase the use of digital technology in their business processes to maximize services. Organizations are unable to carry out digital transformation to maximize the benefits of technology use within the organization. Method: By utilizing the TOE Framework, this study analyzed 85 selected articles using the Prisma protocol. The data analysis technique used bibliometric analysis with VOS viewer and content analysis to identify thematic codes found in the selected articles. Results: There are 4 factors included in the technology component, 6 factors included in the organizational component and 2 factors included in the environmental component. Conclusion: The results of this study explain that the success of digital transformation is not only determined by the technology adopted by the organization, but also the organization's ability to integrate technology with business strategy, organizational capabilities and changes that occur in the organization's external environment